Fast Food Consumption Behavior of Undergraduate Students of Princess of Naradhiwas University - Rongpan, Sudarat; Trisuvan, Phusana; Suwannarat, Nutthatida; Santiparadon, Manutsanun; Hounkong, Kruawan (Princess of Naradhiwas University Journal, 2021)
This is a survey research aiming to study and compare fast food consumption behavior of undergraduate students of Princess of Naradhiwas University which was classified by gender, age, BMI, religion, year, faculty and income. The samples of this study consisted of 341 undergraduate students studying at Princess of Naradhiwas University in academic year of 2020. The sampling size was calculated by Tara Yamane’s formula, and the sampling group was selected using stratified random sampling. The tools used in the study was the questionnaire on fast food consumption which received the confidence level at 0.87. Data were analyzed by using percentage, average, standard deviation, t-test and one-way ANOVA with Fisher’s Least-Significant Different (LSD) multiple comparison tests. The results revealed that students had fast food consumption behavior at a moderate level; eating fast food about 1 to 3 times a week ( X= 2.20, S.D. = 0.31) and give reasons that eating fast food was caused from the public relations ( X= 2.97, S.D. = 0.54) and marketing promotion ( X= 2.91 S.D. = 0.63). Students with different gender, religion, faculty and BMI had no difference in fast food consumption behavior. While the students with different ages, year, and income had different fast food consumption behaviors with statistical significance at 0.05.